Rocket Internet: Organizing a startup factory - Oliver Baumann; Carsten Bergenholtz; Lars Frederiksen; Robert M. Grant; Rebecca Köhler; David L. Preston; Scott Andrew Shane (Journal of Organization Design, 2018)
While some firms build cars or smartphones, Rocket Internet builds companies. The incubator and investment firm has pioneered an extreme approach to new venture creation that is often referred to as a "startup factory:" it rapidly assembles and scales new companies, replicating business models that have been developed elsewhere. Separating the ideation of business models from their execution allows Rocket Internet to specialize on the latter, because it eliminates the need to create an environment that is conducive to both processes. Yet specialization may also be Rocket Internet's largest liability, because it makes the firm dependent on the availability of appropriate (co-specialized) business models. In this edition of the Organization Zoo series, we asked several organizational scientists and scholars of entrepreneurship to share their thoughts on what we can learn from the case of Rocket Internet.
Keywords: 650; Business model replication; Company builder; Imitation; Incubator; New venture creation; Organization design